VP1 of Enterovirus 71 Protects Mice Against Enterovirus 71 and Coxsackievirus B3 in Lethal Challenge Experiment - Chen, Fang-Hong; Liu, Xiong; Fang, Hua-Li; Nan, Nan; Li, Zhan; Ning, Nian-Zhi; Luo, De-Yan; Li, Tao; Wang, Hui (Frontiers in Immunology, 2019)
Enterovirus and Coxsackievirus are the major viruses that cause hand, foot, and mouth disease (HFMD) outbreaks worldwide. Several studies have shown the potential of viral envelope protein 1 (VP1) on providing protective effects from viral strains of different genotypes. However, whether VP1 has the cross-protection in Enteroviruses or Coxsackievirus has not been studied in-depth. In this study, the vp1 gene of Enterovirus 71 (EV71) and Coxsackievirus B3 (CB3) was inserted into the vector pET22b (+) to form the respective expression plasmids pEVP1 or pCVP1, and then transformed into Escherichia coli strain BL21 (DE3). The recombinant EVP1 or CVP1 protein was overexpressed successfully and effectively purified to homogeneity. Then, we determined the cross-protection of VP1 between EV71 and CB3 in a murine model. The results showed that immunization with EVP1 could effectively induce specific IgG against CVP1 and the sera from EVP1-immunized mice could neutralize CB3 with mean titers 1: 440. In contrast, no measurable neutralizing antibodies to EV71 were detected in CVP1-immunized mice. Then, newborn BALB/C mice, whose mother was immunized with EVP1 or CVP1, were administered with different lethal doses of EV71 or CB3. The EVP1 immunized group showed a 90% protective efficacy for a CB3 dosage of 120 LD50, but the CVP1 immunized group showed no significantly different protective efficacy against 15 LD50 of EV71 compared with the BSA immunized group. Hence, EVP1 is a promising subunit vaccine candidate against Enterovirus 71 and Coxsackievirus B3 caused HFMD.